Diskursus Spiritualitas dalam Serat Kalatidha Karya Raden Ngabehi Ranggawarsita: Analisis Wacana Kritik Norman Fairclough - Fifi Amalia; Aris Aryanto; Aisyah Ilham Nurbasith (Kawruh: Journal of Language Education, Literature and Local Culture, 2025)
This study explores the discourse of spirituality in Serat Kalatidha by Raden Ngabehi Ranggawarsita through the lens of Norman Fairclough’s critical discourse analysis. The analysis focuses on the pupuh sinom, which reflects the poet’s spiritual response to moral decay in the zaman edan (age of madness). Using a descriptive qualitative method and literature study technique, the research reveals that Ranggawarsita responds to a corrupted social condition by choosing a spiritual path—distancing himself from worldliness and surrendering fully to God. The spiritual values constructed in the text encompass budidaya (inner and outer effort), eling (self-awareness), waspada (moral vigilance), and ndedonga (devotion through prayer). These four pillars serve as spiritual guidance—an “antidote” for navigating an era filled with uncertainty. Through the discourse analysis framework, Serat Kalatidha is revealed as a depiction of Ranggawarsita’s spiritual journey, born from his inner anxiety over a chaotic and unjust world.